(untitled) (Journal of Economic Research & Business Administration, 2015)
This article explores the famous strategies of business development identified by well-known international researches. In this work, Japanese business philosophy of business development- «Kaizen» was considered. The analyzed sources prove that Kaizen can be used not only by big companies, but it can be successfully used by small and medium enterprises. Furthermore, the difference in running business by western companies and Japanese companies was considered. In particular, it was found that western companies are more focused on innovation, while their Japanese counterparts focus their efforts on involving all personnel, beginning from working class to top management, in “Kaizen”. Alternative point of view and critique for the Japanese framework were provided by the professor of Harvard Business School Michael Porter. In the last section, based on the examples of international researches, the importance of integrated marketing communications in creating of sustainable competitive advantage was emphasized.